PENGARUH PRIOR OPINION, DEBT DEFAULT, DAN FINANCIAL DISTRESS TERHADAP OPINI GOING CONCERN - Mega Arisia Dewi; Ananda Putri Rahayu (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2026)
This research analyses the effect of prior opinion, debt default, and financial distress on giving an audit going concern opinion. The giving an audit going concern opinion is caused by auditor doubt towards companies’ business sustainability in the future. The research applies quantitatively. Furthermore, the population consists of Properties and Real Estate companies listed in the Indonesia Stock Exchange (IDX) during 2022-2024. The data were collected using purposive sampling with 105 data observations from 35 samples companies. Moreover, the study adopted debt default which was referred to as Debt to Equity Ratio (DER) and financial distress which was referred to as G-Score model. The data were analysed using logistic regression. The research shows that both prior opinion and financial distress have a positive effect on giving an audit going concern opinion. However, debt default does not affect giving an audit going concern opinion. These findings contribute to the management and auditor in understanding factors which can affect giving an audit going concern opinion.